Orthodontic consequences of airway inadequacy due to adenoids - Bara' S Minwah; Afrah Kh Al-Hamdany; Dawood S Allous (University of Mosul, College of Dentistry, 2004)
The current study was performed to investigate the possible association bet-ween nasopharyngeal airway inadequacy due to enlarged adenoid and some dento-alveoular characteristics in subjects 3-17 years old in Mosul City. Twenty four patients (12 males and 12 females) were randomly selected from patients who admitted to Ear Nose and Throat Department at Al-Zahrawi Teaching Hospital in Mosul City and who indicated for adenoidectomy to relieve severe nasal obstruction. Sixteen variables were recorded and analyzed using Statistical Package for Social Sciences system loaded on Pentium IV computer. The results proved that a significant correlation existed between nasopharyngeal airway inadequacy due to enlarged adenoid and some dentoalveoular characteristics and females were having high incidence of tonsillar enlargement than males.